Editorial: a non‐dietary treatment for coeliac disease—two steps forward, one step back?. Issue 8 (7th October 2019) - Mitchell, Hannah; Garg, Mayur
Abstract : LINKED CONTENT This article is linked to Truitt et al and Truit and Anderson papers. To view these articles, visithttps://doi.org/10.1111/apt.15435 andhttps://doi.org/10.1111/apt.15494 .